TRADITIONAL RISK FACTORS FOR CARDIOVASCULAR DISEASES IN SYSTEMIC SCLEROSIS AND THEIR RELATIONSHIP TO STRUCTURAL CHANGES OF THE HEART - E. O. Saad; L. P. Ananyeva; D. S. Novikova; R. T. Alekperov (Научно-практическая ревматология, 2017)
Objective: to determine the frequency of traditional risk factors (TRFs) for cardiovascular diseases (CVD) in patients with systemic sclerosis (SS) and to analyze their relationship to the clinical manifestations of SS, as well as to structural changes, as evidenced by echocardiography (EchoCG).Subjects and methods. The investigation enrolled 125 patients with SS and 50 sex- and age-matched, apparently healthy individuals included in a control group. Standard electrocardiography was performed in all and EchoCG – in 121 patients. The Systematic Coronary Risk Evaluation (SCORE) scale was used to assess the risk of fatal CVD in 100 patients with SS and in 47 control individuals within 10 years.Results and discussion. The frequency of TFRs in patients with SS was not significantly different from that in the control group, except for the occurrence of hypercholesterolemia and increased body mass index (BMI). In SS, BMI >25 kg/m2 was observed significantly more often and the frequency of hypercholesterolemia was lower than in the controls (p <0.018). Hypertension and diabetes mellitus were slightly more frequently encountered in SS patients than in the controls, but this difference was insignificant. Taking into account the Russian Society of Cardiology (RSC) guidelines, the cardiovascular risk (CVR) was assessed with the SCORE scale. A very high CVR was much more common in SS and a moderate CVR was much more frequently seen in the control group. There were no substantial differences in the frequency of low and high CVRs. SS is characterized by the increased frequency of high total CVD risk as compared to the controls. Hypertension, overweight, and over 50 years of age were associated with more obvious structural heart disease.Conclusion. TRFs make a substantial contribution to the formation of a high CVR in patients with SS, promoting the development of atherosclerosis and its complications. Assessment of TGFs in SS patients will facilitate identifying patients at high risk for cardiovascular death and timely prescribing therapy. Hypertension is an important TGF that in SS is associated with considerable structural changes in the heart; therefore adequate blood pressure control is of importance in improving SS prognosis especially in patients older than 50 years.